Solve this :


Q . 10 .         S o l v e   t h e   s y s t e m   o f   e q u a t i o n s   : log a   x   log a   x y z   =   48 log a   y   log a   x y z   =   12 ,   a   >   0 ,   a     1 . log a   z   log a   x y z   =   84

Hi, 



logax×logaxyz=48....1logay×logaxyz=12....2logaz×logaxyz=84....3Add the three equation we get logaxyzlogax+logay+logaz= 144logaxyz×logaxyz= 144 logaxyz= 12 or -12 now case 1, when logaxyz= 12then from equation 1 , 2 ,3 logax=4812= 4 so x = a4logay=1212=1 so y = a1logaz=8412= 7so z = a7now case 2, when logaxyz=- 12then from equation 1 , 2 ,3 logax=48-12=- 4 so x = a-4logay=12-12=-1 so y = a-1logaz=84-12= -7so z = a-7

  • 1
What are you looking for?